Field notes contributed by Joe Schaufenbuel, May 30, 1982 - Schaufenbuel, Joseph P.et al (1982)
Field notes were contributed by Joe Schaufenbuel. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1982. Epson - sheet feed